Filipinos' access and exposure to ICT: A general overview based on the National ICT Household Survey - Aubrey D. Tabuga; Carlos C. Cabaero (Philippine Institute for Development Studies (PIDS), 2021)
Information and communication technology (ICT) is now considered a basic necessity in the digital world. It is noted that it permeates all aspects of life as it provides better and quicker ways for people to learn, interact, and gain access to information. In the Philippines, the 2019 National ICT Household Survey marked the first effort by the government to map the general ICT landscape in the country which examined among others the use of cellular phones and computers and extent of Internet usage and online financial transactions. This survey was administered to a nationally representative sample of households and individuals in the country. This paper provides a general overview of ICT use based solely on this survey. The findings show that there is differentiated access to ICT across sub-national regions. There remains a non-negligible proportion of individuals who do not have access to ICT partly due to lack of infrastructure. There is also much to improve in terms of using ICT for economic purposes such as acquiring skills, doing online financial transactions, and conducting business.
Keywords: 330; ICT; online work; e-entrepreneurship; NICTHS; Philippines